Development of a Chemistry E-module with a STEM-Integrated Project Based Learning Model on Chemical Equilibrium Material - Ibrahim, Taufik Ali; Sutiani, Ani (Universitas Negeri Medan, 2025)
The purpose of this study is to develop an e-module with an Integrated Project Based Learning (PjBL) Model for Science, Technology, Engineering, and Mathematics (STEM) on Chemical Equilibrium, and to measure the level of validity and student response to the e-module. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The research subjects were 39 students of class XI A Plus of SMA Negeri 1 Kutacane in the 2024/2025 academic year. The instruments used included an interview questionnaire, a validation questionnaire from material and media experts, and a student response questionnaire. The validation results by material experts showed a validity level of 97.2%, while the validation results by media experts showed a validity level of 97.3%, both of which are in the very valid category. Meanwhile, the results of the level of practicality by teachers towards the e-module were 92% which was said to be very practical, and the results of the student response questionnaire towards the e-module showed an average value of 92%, which was included in the very practical category.